2015
DOI: 10.3892/ijmm.2015.2199
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane prevents doxorubicin-induced oxidative stress and cell death in rat H9c2 cells

Abstract: Sulforaphane, a natural isothiocyanate compound found in cruciferous vegetables, has been shown to exert cardioprotective effects during ischemic heart injury. However, the effects of sulforaphane on cardiotoxicity induced by doxorubicin are unknown. Thus, in the present study, H9c2 rat myoblasts were pre-treated with sulforaphane and its effects on cardiotoxicity were then examined. The results revealed that the pre-treatment of H9c2 rat myoblasts with sulforaphane decreased the apoptotic cell number (as show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 59 publications
(55 reference statements)
2
46
0
Order By: Relevance
“…Evidence indicated that inhibition of Nrf2 by either genetic manipulation or an inhibitor can increase the sensitivity of ovarian and hepatocellular carcinoma cell lines to AD . Although it remains unclear whether Nrf2 also participates in the action of AD‐mediated topoisomerase II activity dysregulation, other and our data all suggest that activation of Nrf2 can suppress AD‐induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 49%
“…Evidence indicated that inhibition of Nrf2 by either genetic manipulation or an inhibitor can increase the sensitivity of ovarian and hepatocellular carcinoma cell lines to AD . Although it remains unclear whether Nrf2 also participates in the action of AD‐mediated topoisomerase II activity dysregulation, other and our data all suggest that activation of Nrf2 can suppress AD‐induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 49%
“…31 As shown in Figure 5a, Dox caused an approximately 2.7-fold increase in intracellular ROS generation as monitored by DCF fluorescence, which was significantly decreased by SPRC ( P <0.01). Moreover, consistent with recent studies, 31, 32 Dox-treated cells revealed the release of proapoptotic mitochondrial protein cytochrome c into cytosol. In contrast, SPRC prevented Dox-induced cytochrome c release ( P <0.05; Figure 5b).…”
Section: Resultsmentioning
confidence: 75%
“…45 The release of cytochrome c from mitochondria to cytosol, and dissipation of ΔΨm , is linked to Dox-mediated apoptotic signaling and mitochondrial dysfunction. 31 On the other hand, oxidative stress through cumulative Ca 2+ and mitochondrial dysfunction causes depletion in ATP necessary in the process of myocardial fiber contractions. 46, 47 It can also be a basis for pathological changes in Ca 2+ regulation through SERCA2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DOX-induced cardiac toxicity appears to be multifactorial, the most thoroughly investigated hypothesis has been the formation of reactive oxygen species (ROS) and there is evidence pointing to cardiac mitochondria as primary targets of the toxicity of DOX [3]. The quinone moiety of DOX may form semiquinone radicals by oneelectron reduction.…”
Section: Introductionmentioning
confidence: 99%